Особливості змін композиційної структури деревних угруповань Тростянецького парку - Iljenko, O.O.; Medvedev, V.A.; Shulga, S.O.; Andriyko, M.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2014)
The results of researches of basic progress trends and orientation of changes of composition structure of decorative groups of flatly-landscape part of Dendropark Trostjanets in the period from 1960 to 2012 are elucidated. The examples of changes of taxonomical composition of decorative groups of different composition type during this period are presented.